2014
DOI: 10.1159/000356020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Immunosuppressive Drugs on Immune Cells from Young and Old Healthy Persons

Abstract: Background: Life expectancy, as well as the average age of patients undergoing solid organ transplantation, increases constantly. Consequently, immunosuppressive therapy is no longer limited to young organ recipients. Objective: Here, we investigate how different types of immunosuppressive therapy, namely the calcineurin inhibitors cyclosporin A and tacrolimus, as well as the mTOR inhibitor rapamycin, affect the function of immune cells in young and elderly persons. Methods: Proliferation, cell viability, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…TL over time was similar in our 2 GVHD prophylaxis groups. To our knowledge, similar assessments have not been published previously; However, a relevant study of the effect of different immunosuppressive drugs on lymphocyte TL in healthy individuals was published by Welzl et al in 2014 [45]. Their in vitro results showed that CsA and Tac had a more pronounced prosenescence effect compared with rapamycin after short-term immunosuppressive treatment, with significantly less reduction of TL in peripheral blood mononuclear cells cultured in the presence of rapamycin.…”
Section: Discussionmentioning
confidence: 65%
“…TL over time was similar in our 2 GVHD prophylaxis groups. To our knowledge, similar assessments have not been published previously; However, a relevant study of the effect of different immunosuppressive drugs on lymphocyte TL in healthy individuals was published by Welzl et al in 2014 [45]. Their in vitro results showed that CsA and Tac had a more pronounced prosenescence effect compared with rapamycin after short-term immunosuppressive treatment, with significantly less reduction of TL in peripheral blood mononuclear cells cultured in the presence of rapamycin.…”
Section: Discussionmentioning
confidence: 65%
“…The question remains why immunological aging does not reverse even when adequate graft function is achieved post‐KTx. As stated above, we cannot formally rule out that IS drugs prevent the restoration of thymic output, telomere length and reversal of memory T‐cell differentiation status . However, a more likely explanation might lie at the epigenetic level.…”
Section: Discussionmentioning
confidence: 87%
“…This finding suggests that the immune systems of young and older patients differ. Certainly, differences between immune systems of young and older animals have been demonstrated [17,39,40] . Book et al [17] have shown that older animals have significantly weaker responses to new alloantigen stimulation than young animals.…”
Section: Discussionmentioning
confidence: 99%